Postmenopausal exogenous hormone therapy and Melanoma risk in women: A systematic review and time-response meta-analysis. (October 2020) - Tang, Xiaoling; Zhang, Hongcan; Cui, Ying; Wang, Liqin; Wang, Zhu; Zhang, Yajing; Huo, Jinzhi; Cai, Jinfeng; Rinaldi, Giulia; Bhagavathula, Akshaya Srikanth; Xiaopeng, Ying
Abstract: A favourable option to management symptoms during menopausal transition is menopausal hormone therapy (MHT) but relation among MHT and risk of melanoma is controversial. This study aims to identify, analyse and present the evidence surrounding post-menopausal exogenous hormone therapy and the risk for melanoma in women. A systematic searches of database was conducted in PubMed/MEDLINE, Scopus, and Cochrane without time, region, and language restrictions from inception to April 2020. The DerSimonian and Laird random-effects model was used to estimate combined risk ratio (RR) and 95% confidence intervals (CI). Subgroup analysis and time-response analysis was conducted based on the formulation of used hormone and length of hormone therapy. Combined results from fourteen studies that containing 19 arms with 1, 164, 077 participants which 4273 of them had melanoma cancer showed increase risk of melanoma in the hormone-treated versus control group 1.14 (95% CI 1.05–1.24, I2: 21%). The stronger and significant relationship between MHT and risk of melanoma was in participants who used oestrogen formulation (RR 1.32, 95% CI 1.17–1.49, I2 = 0%). Moreover, a significant non-linear time-response relation between MHT and melanoma was also in initial three years of MHT (Coef1 = 0.2423, p1 < 0.01). This study reveals a significant direct relationship between the MHT and risk of melanoma in postmenopausal women.